PENGARUH PENGUNGKAPAN ESG DAN RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN - Gultom, Rocia Haki Maria; Alexander, Nico (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to provide empirical evidence regarding the influence of ESG Disclosure Score, profitability, leverage, size, liquidity, and activity ratio as independent variables on firm value as the dependent variable. The population of this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2023. The sampling method used in this research is purposive sampling, resulting in 107 companies with a total of 321 data points that meet the predetermined sample criteria. The data analysis and hypothesis testing method employed in this study is multiple regression analysis. The results show that the activity ratio has an impact on firm value, as inventory turnover indicates high company revenue, thereby increasing firm value. Size also influence firm value, showing that large companies experience a decline in efficiency in overseeing operational activities carried out by management. On the other hand, ESG Disclosure Score, profitability, leverage, and liquidity do not affect firm value.